Acylphloroglucinols from Elaphoglossum crassipes: Antidepressant-like Activity of Crassipin A - Socolsky, Cecilia (2012)
Nine new terpenylated acylphloroglucinols, crassipins A-I, were isolated from the rhizomes and roots of the fern Elaphoglossum crassipes, and their structures were elucidated by analysis of spectroscopic data and chemical derivatization. The absolute configurations of some of the compounds were established by CD and VCD in combination with a quantum mechanical method. Crassipin A (1), the major acylphloroglucinol of the Et2O extract of E. crassipes, as well as its peracetylated derivative (8), displayed antidepressantlike activity in a mouse forced-swimming test when administered orally at a dose of 15 mg/kg.